The use of mobile app (Fluency in English) to enhance the speaking English ability among Chinese college students - Chen, Li; Yordchim, Suwaree; Sukamolson, Suphat (Edelweiss Applied Science and Technology, 2025)
With the rapid advancement of technology, mobile-assisted language learning (MALL) has emerged as a powerful tool for enhancing students’ English-speaking proficiency. This study explores the effectiveness of using the Fluency in English app as a digital learning platform to improve college students’ English speaking skills. By integrating interactive exercises, AI-driven pronunciation feedback, and real-time communication features, the app provides learners with a flexible and immersive language learning experience. The research examines students’ speaking performance before and after using the app through a mixed-methods approach, incorporating quantitative assessments and qualitative feedback. Findings indicate that students demonstrate significant improvements in accuracy, coherence, and flexibility. The results suggest that mobile apps like Fluency in English can be effective tools for improving English-speaking skills in college students.